Vliv únavy půdy a závlahy na hospodářské vlastnosti a minerální výživu jabloní odrůdy ‘Gala Brookfield’ - Martin Mészáros (VÝZKUMNÝ A ŠLECHTITELSKÝ ÚSTAV OVOCNÁŘSKÝ HOLOVOUSY s.r.o., 2021)
Replant disease represents an important obstacle in replantation of horticultural crops. There is a lack of knowledge about the influence of replant disease on nutritional status of fruit trees. This study was focused on comparison of the growth and production characteristics and nutritional status of apple trees ‘Gala Brookfield’ among different location according to replant problems and used irrigation strategy. In this trial, growth intensity, flowering intensity, yield, fruit quality, and leaf mineral content of N, P, K, Mg, and Ca were assessed. We found that the apple trees planted in replant soils grows 30 % less and bears 16 % less fruit than those in fresh soils. They are more susceptible to water deficit, documented by lower yield and mean fruit weight. Lower yield efficiency and fruit quality of the vigorously growing apple trees in fresh soil shows to the need for establishment of better light conditions in orchard. The nitrogen content was more related to the proportion between generative and vegetative growth, whereas the phosphorus, potassium, magnesium, and calcium were more site specific. Generally, apple trees are prone to accumulate more magnesium in leaves on fresh soils. The use of regulated deficit irrigation with intense fruit thinning may require corrections of the fertilization management with P, Mg, and Ca.